1989
DOI: 10.1111/j.1365-2826.1989.tb00068.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Receptors on Ovine Pars Tuberalis: Characterization and Autoradiographicai Localization

Abstract: The functional significance of the pars tuberalis (PT) of the mammalian adenohypophysis has remained an enigma (1, 2). One view of its function is that it acts as an auxiliary gland to support the endocrine role of the pars distalis (PD) (2), as it has been shown to contain immunocytochemically identifiable thyrotrophs and gonadotrophs (1). Many of the cells of the PT are, however, ultrastructurally unique suggesting an independent function for this tissue. Our recent demonstration that the PT of the rat is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
96
0
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(103 citation statements)
references
References 17 publications
6
96
0
1
Order By: Relevance
“…In a recent competitive binding study it has been shown that ML23 has a very low potency in inhibiting the binding of 125I-labelled melatonin (0062%) in crude membrane preparations from the hypothalamus of male rats (English & Arendt, 1988). This result has also been confirmed in preparations from the pars tuberalis of sheep (Morgan et al, 1989).…”
Section: Discussionsupporting
confidence: 72%
“…In a recent competitive binding study it has been shown that ML23 has a very low potency in inhibiting the binding of 125I-labelled melatonin (0062%) in crude membrane preparations from the hypothalamus of male rats (English & Arendt, 1988). This result has also been confirmed in preparations from the pars tuberalis of sheep (Morgan et al, 1989).…”
Section: Discussionsupporting
confidence: 72%
“…At equimolar concentrations, the level of BRET detected was independent of the receptor expression levels (data not shown). BRET was observed at receptor levels as low as 20 fmol/mg of protein, a concentration similar to those observed in native tissues such as the retina (70 fmol/mg) (18) and the hypophysal pars tuberalis (40 fmol/mg) (19) indicating that the constitutive homo-and hetero-dimerization detected by BRET did not result from over-expression and could reflect a physiological reality.…”
Section: Detection Of Mt1r and Mt2r In Hek 293mentioning
confidence: 72%
“…The pars tuberalis of the pituitary binds ['251]iodomelatonin in the Syrian hamster, the rat (18) and the sheep (20) and is the most intensely labelled region found in all three species (19) (present study and unpublished observation). The influence of photoperiod on the pars tuberalis has previously been shown in the Djungarian hamster where cells in this region exhibit distinct morphological and immunocytochemical changes in animals kept under different light regimes (32, 33).…”
Section: Discussionmentioning
confidence: 94%
“…(43) and separated by HPLC (18,20) to provide a ligand with close to the maximal specific activity of ca. 2,000 Ci/mmol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation